Factors influencing non-adherence to opioids in cancer patients: A mixed-methods cross-sectional study - Rattaphol Seangrung (2022)
Background: Strong opioids are mainly utilized to attenuate pain in cancer patients. Adherence to analgesic drugs significantly promotes adequate pain management and improves quality of life. We aimed to identify the factors influencing non-adherence to strong opioids in cancer patients. Methods: A descriptive, cross-sectional, two-phased, mixed methods design was conducted prospectively to evaluate a cohort of 101 cancer patients who are currently prescribed strong opioids from a pain clinic in Thailand between January and March 2018. Participants were asked to complete a questionnaire that included the following sections: general characteristics; the Medication Taking Behavior in Thai (MTB-Thai) for assessing adherence to medications; and factors influencing nonadherence, which were analyzed using multivariate logistic regression. In addition, face-to-face in depth interviews were conducted with patients showing non-adherence to strong opioids (MTB-Thai score ≤21) and analyzed using thematic content analysis. Results: Of 101 cancer pain patients that completed the questionnaire, 39.6% showed non-adherence to strong opioids. Illness understanding (P=0.047) and the use of more than three types of pain medication (P=0.032) were significant factors influencing non-adherence. Qualitative analysis indicated that fear of long-term outcomes, opioid side effects, ineffective pain control, attempts to make the regimen more acceptable, poor understanding, and non-acceptance of disease related to non-adherence. Conclusion: Non-adherence to opioids for cancer patients is a common problem. Awareness of patient factors, medication-related factors, and illness-related factors will provide the knowledge and adequate advice that may enhance adherence to medications.